Modelling of stark effect in InAs-AlGaSb multi-quantum wells - Geri Kibe AK Gopir, (Universiti Kebangsaan Malaysia, 2000)
The Stark effectina (20)InAs(6)As-(6)Al0.1Ga0.9 Sb multi-quantum well structure was theoretically modelled using the electric-field-perturbed formulation of the empirical pseudopotential method. An external electric field of up to 4.0 x 1()5 V cm-! was applied along the axis of the multi-quantum well structure and its effect on the energy level, localisation and optical transition of the lowest electron and hole states were investigated. The perturbation produced Wannier-Stark localisation and a red Stark shift for this type II semiconductor heterostructure. The calculated optical gap decreased down to 10 meV with the corresponding principal momentum matrix elements, along x polarisation, remain basically constant at a.u.(atomic unit). This property makes the III-V semiconductor heterostructure potentially attractive for use as a field-tunable device in the infrared spectra of 10-100µm.